Trend of Poisoning in Muzaffarabad (AJK) (Medical Forum Monthly, 2024)
Objective: The objective of this study is to determine the trend of poisoning in Muzaffarabad AJK.Study Design: Retrospective study.Place and Duration of Study: This study was conducted at combined Military Hospital (CMH) Muzaffarabad (AJK) during the period of 1st January 2009 to 31st December 2010.Material& Methods: One hundred & forty cases of poisoning was brought in hospital. Information regarding Age, Gender, demography, manner, time of occurrence, and patient outcome was confirmed from hospital records and collected data was analyzed.Results: There were 98 female and 42 mate victims involved in this study and maximum cases belong to second and third decade of life (23.57% and 48.57% respectively. Most common manner of poisoning was suicidal / attempts. Most incidences of poisoning occur in month of June and an organophosphorous compounds was leading cause of poisoning followed by Benzodiazepines.Conclusion: Organophosphorous compounds are the major chemical agents which pose a health threat particularly to young people.